Micro-indentation of metal matrix composites: a 3D finite element analysis - Pramanik, Alokesh; Zhang, L.; Arsecularatne, J. (Engineers Australia, 2012)
This paper investigates the inhomogeneous behaviour of metal matrix composites subjected to micro-indentation by a spherical indenter, using 3D finite element analysis. This includes the effects on hardness of volume fraction of reinforced particles and (indenter):(particle diameter) ratio. It was found that increasing the volume fraction of reinforced particles and the (indenter):(particle diameter) ratio increases the resistance to deformation of the composite. The hardness varies in a complex way with the changes of load, volume percentage of particles and (indenter):(particle diameter) ratio.